Anti-feminist expressions on YouTube. A discursive analysis of the youtuber Roma Gallardo - del Pino Díaz, David (CIC. Cuadernos de Información y Comunicación, 2023)
The growing number of youtubers critical of the feminist movement has been a real event in recent years, coinciding with the consolidation of the fourth feminist wave since 2018. The aim of this paper is to analyse the ideological structure of the well-known youtuber Roma Gallardo. To this end, both a quantitative analysis using the Social Blade tool and a qualitative analysis using the discourse analysis technique on a sample of 20 videos between 2019 and 2022 are used. The results show that Roma Gallardo’s discourse is articulated around three ideological axes: the ridiculing of feminism, the recomposition of the male social space and the trivialisation and mockery of the violence suffered by women. Finally, the youtube’s discursive strategy seeks to impose a view of social reality without ideological impositions.
Keywords: Anti-feminism; male backlash; manosphere; YouTube; sexual violence